Management of cervical heterotopic pregnancy with inevitable miscarriage - R., Shyamala; Srikumar, Saranya; K., Radhamany (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The objective is to report a case of successful treatment of heterotopic cervical pregnancy resulting from IVF–ICSI conception. Case report from Amrita Institute of Medical sciences: a tertiary care referral hospital. A 47-year-old Primigravida, diagnosed with heterotopic cervical pregnancy at 6 weeks of gestation, presented with significant first trimester vaginal bleeding. Under IV sedation, Transvaginal ligation of descending cervical branches of the uterine arteries arrested the bleeding. The cervical pregnancy was successfully aborted with minimal bleeding and the intrauterine pregnancy was successfully maintained till 32 weeks, after which she required emergency preterm LSCS in view of Severe preeclampsia superimposed on chronic hypertension a non-reassuring non-stress test (NST). The intervention applied maybe used in treatment of heterotopic cervical pregnancy in a low resource setting to control the bleeding.